Kvalitetsarbete i grotskotning - Parlow, Hannes (SLU/School for Forest Management, 2012)
This study was carried out at the request of the Swedish forest company Sveaskog which is an important producer of logging residues (branches and tops) intended for energy production. The company wanted to increase the average dry content to 60 percent in their delivered logging residues. At the time when this study was initiated, the dry content in the chipped logging residues originating from the Bergslagen district was at 52 percent. The aim of the study was to find out how windrows of logging residues could be arranged in order to help obtain desired properties such as increased dry content. Sveaskog had developed a system for evaluation of windrows and a standardized form was utilized to describe different properties of the windrows. The form consisted of six major sections, each looking at different quality parameters. Emphasis was directed towards evaluating the planning, preparation, and choice of site for the landing area and to see if local site conditions had been utilized to help improve the final windrow properties. Additional information concerning overall design of the windrow and the quality of the covering, as well as the extent of contamination in the windrows was also collected. There was no coherence between the six quality parameters investigated and the measured dry content. Furthermore, the number of months during which the logging residue had been stored in a windrow was found to be of negligible importance. On the contrary however, the time of the year during which the material was transported out of the stand appeared to affect measured dry content the most. Hauling in the period of April to October resulted in a higher dry content compared to the period between November and March. There were large differences between the dry content of windrows at the same sites which added to the sources of error in this study. In addition, it was impossible to accurately estimate the degree of contamination inside the windrows because of the amount of snow present during the time when the field work was conducted. Another problem in this study was that no data on dry content for individual windrows could be obtained; only averages for the entire site were available. This made it impossible to evaluate effects due to factors such as location of individual windrows and distance from windrows to the nearest standing forest, since most sites consisted of many different windrows. When performing a new similar study it would therefore be more appropriate to measure dry content on every single windrow instead of only obtaining overall averages. Keywords: dry content, moisture content, windrow (branches and tops)